3D Printed carbon fibre reinforced polyamides in high temperature Poliamida diperkuat gentian karbon cetakan 3D pada suhu tinggi - Norazyan Rudi Hartono; Nisa Naima Khalid; Nabilah Afiqah Mohd Radzuan; Abu Bakar Sulong (Penerbit Universiti Kebangsaan Malaysia, 2003)
In additive manufacturing, polymer composites are often produced by using fuse deposition modeling (FDM) methods which usually have a clear effect on layer by layer due to incomplete bonding once it is been printed. FDM is one of the widely used 3D printing technology due to its fast printing speed and affordable cost. The mechanical characteristics of composite printed using the FDM technology are affected by the printing parameters of the FDM machine. The mechanical and tensile characteristics of polymer printed using FDM technology are also affected when it is exposed to high temperature. Therefore, this study is to identify the effect of high temperature towards the mechanical performance and tensile characteristics of FDM printed with 2 different printing temperature . A total of 18 samples with 2 different printing temperatures, are tested through a tensile test at temperature of 190°C, 200°C, and 210°C, scanning electron microscope (SEM), thermogravimetric analysis (TGA), and dynamic mechanical analysis (DMA).